2020
DOI: 10.14715/cmb/2020.66.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The application of DNA molecular markers in the study of Codonopsis species genetic variation, a review

Abstract: Codonopsis genus is comprised of species that are perennial plants primarily distributed across all east, southeast, and Central Asia. The most famous species of Codonopsis are C. tangshen, C. lanceolate, and C. pilosula. The records showed that they have a long story usage as traditional Chinese medicines, as they were alleged to be able to intensify the spleen and the lung as well as enriching blood and engendering liquid. Certain species have a culinary value in southern China and Southeast Asia, where they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Although there is no clear clinical evidence showing that combination therapy is more effective than anti-inflammatory mono-therapy, some studies have shown that dexmedetomidine exerted anti-inflammatory influence by reducing the level of inflammatory factors in serum, however, its upstream mechanism remains poorly understood at present (25). There are still some inadequacies in the present study, as we have not conducted a detailed analgesic study on drug subscales, nor the overall analgesic effect and prognosis for children have been determined (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 88%
“…Although there is no clear clinical evidence showing that combination therapy is more effective than anti-inflammatory mono-therapy, some studies have shown that dexmedetomidine exerted anti-inflammatory influence by reducing the level of inflammatory factors in serum, however, its upstream mechanism remains poorly understood at present (25). There are still some inadequacies in the present study, as we have not conducted a detailed analgesic study on drug subscales, nor the overall analgesic effect and prognosis for children have been determined (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 88%
“…In this study, the Spearman correlation analysis showed the close and positive relationship between these fungi together with bacteria and the environmental factors including AN, AP, TN and TP, UE, CAT and ACP (Figure 8). These factors may be associated with replant problem under CC system (Table 2), which suggests the possible negative effects of microbial diversity on the environmental factors under CC system [39][40][41][42]. Figure 6.…”
Section: 11benefit Of Plants As Results Of Changes In Soil Microbiamentioning
confidence: 99%
“…This suggests that low-dose insulin combined with electrolyte therapy is related to the alleviation of inflammatory response. Thus inhibiting the levels of inflammatory factors may be one of its therapeutic mechanisms (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%